Knowledge-based systems techniques and applications - Leondes, Cornelius T. (San Diego, Calif. ; London : Academic, 2000)
The design of knowledge systems is finding myriad applications from corporate databases to general decision support in areas as diverse as engineering, manufacturing and other industrial processes, medicine, business, and economics. In engineering, for example, knowledge bases can be utilized for reliable electric power system operation. In medicine they support complex diagnoses, while in business they inform the process of strategic planning. Programmed securities trading and the defeat of chess champion Kasparov by IBM's Big Blue are two familiar examples of dedicated knowledge bases in combination with an expert system for decision-making. With volumes covering "Implementation," "Optimization," "Computer Techniques," and "Systems and Applications," this comprehensive set constitutes a unique reference source for students, practitioners, and researchers in computer science, engineering, and the broad range of applications areas for knowledge-based systems.
v. 1. Implementation -- v. 2. Optimization -- v. 3. Computer techniques -- v. 4. Systems and applications.
Keywords: Expert systems (Computer science).; Knowledge management; Electronic books